Infectious diseases genomic surveillance capacity in the Caribbean: A retrospective analysis of SARS-CoV-2Research in context - Mentor Ali Ber Lucien; Martin S. Forde; Marc R. Isabel; Maurice Boissinot; Sandra Isabel (Elsevier, 2023)
Summary: Background: The ongoing coronavirus diseases 2019 (COVID-19) pandemic with its numerous variants of concern has shown the need to have a robust and complete global infectious diseases genomic surveillance network worldwide. Various clinical and research institutions have stepped up to perform SARS-CoV-2 sequencing thus enhancing the understanding of this virus' global evolution. However, given that genomic sequencing capacities and capabilities are not available in every region or country, significant gaps exist, which lead to geographic blind spots. One such region is the Caribbean. This paper measures the Caribbean region's SARS-CoV-2 genomic sequencing capacity and highlights the need to improve further regional genomics surveillance capacities and capabilities, which are essential for efficient health interventions for infectious diseases. Methods: A map showing SARS-CoV-2 sequences available for each Caribbean Island was constructed using SARS-CoV-2 genomic, epidemiological and populational data obtained from GISAID, the World Health Organization, the United Nations, and the World Bank. The number of reported SARS-CoV-2 cases and the proportion of cases sequenced in each Caribbean Island was then analysed by the Gross Domestic Product per capita and political status. Findings: As of August 6, 2022, the number of SARS-CoV-2 sequences from the Caribbean are underrepresented with only 40,190 (1.07%) of the over 3.76 million documented cases sequenced, which is further exacerbated by a disparity based not only on the country's income but also on its political status (sovereign country versus dependent or integrated) and accessibility to sequencing technologies. There are a limited number of sequencing centres based in the Caribbean islands with the majority located on the American and European continents. Using mobile sequencing technologies while concomitantly investing in data analysis training could lead to greater and more sustainable coverage. Interpretation: Considering the Caribbean region's dispersed heterogeneous populations, varying political regimes, and resource-constrained healthcare systems, further development of local next-generation sequencing capacity and capabilities in the Caribbean region is needed to achieve global public health goals. Funding: No funding source was required for this study.